Connecting the science and practice of implementation – applying the lens of context to inform study design in implementation research - Harvey, Gillian; Rycroft-Malone, Jo; Seers, Kate; Wilson, Paul; Cassidy, Christine; Embrett, Mark; Hu, Jiale; Pearson, Mark; Semenic, Sonia; Zhao, Junqiang; Graham, Ian D. (Frontiers in Health Services, 2023)
The saying ‘horses for courses’ refers to the idea that different people and things possess different skills or qualities that are appropriate in different situations. In this paper, we apply the analogy of ‘horses for courses’ to stimulate a debate about how and why we need to get better at selecting appropriate implementation research methods that take account of the context in which implementation occurs. To ensure that implementation research achieves its intended purpose of enhancing the uptake of research-informed evidence in policy and practice, we start from a position that implementation research should be explicitly connected to implementation practice. Building on our collective experience as implementation researchers, implementation practitioners (users of implementation research), implementation facilitators and implementation educators and subsequent deliberations with an international, inter-disciplinary group involved in practising and studying implementation, we present a discussion paper with practical suggestions that aim to inform more practice-relevant implementation research.